Assessing the Effectiveness of a Research-Driven Biochemistry Laboratory Manual in Enhancing Student Cognitive Learning Outcomes and Business Awareness - Prapti Sedijani; Dewa Ayu Citra Rasmi; Kusmiyati; Elga Amelinda Nathnia (Postgraduate, University of Mataram, 2024)
This study examines student responses upon the implementation of Biochemistry Laboratory Manual which focused on science-economics. The manual was implemented on Biochemistry poracticum classes for 3 consecutive schedules. Students' cognitive, affective, and psychomotor learning outcomes were recorded that implies their responses to the topic. Validated questions and questionnaires were used and were administered before the first and after the third round of practicum classes. Data analysis employed Student T-tests. It was revealed that the implementation of the Laboratory Manual moderately enhances biochemistry learning achievements (N-Gain) and the students responded positive and very positive toward the topic at 80% and 18% respectively.